Assessment of Liquefaction Potential Based on CPT Data in Tuban Police Headquarters Apartment Building Construction Project - Ivan Triandi; Wahyu Satyaning Budhi; Ganda Surahman (Department of Civil Engineering, Politeknik Negeri Bandung, 2026)
Liquefaction is a seismic phenomenon where saturated soil loses its shear strength and transforms into a liquid state due to earthquake-induced cyclic loading. While primarily occurring in sandy soils, this study evaluates the liquefaction potential at the Tuban Police Headquarters Apartment project, characterized by clayey deposits in a former paddy field area. Given Tuban's significant seismic activity, a thorough assessment is imperative. This research employs a quantitative approach using the semi-empirical NCEER method developed by Youd and Idriss (2001). The evaluation is based on primary data from the Cone Penetration Test (CPT) at two distinct points, S-1 and S-2. The analysis involves calculating the Cyclic Stress Ratio (CSR) as the seismic demand and the Cyclic Resistance Ratio (CRR) as the soil’s liquefaction resistance. A Safety Factor (FS) is then calculated for each soil layer to determine stability. Results indicate that FS values range from 3.1 to 8.9 at S-1 and from 3.4 to 9.1 at S-2. Since all calculated FS values exceed the critical threshold of 1.0, the site is classified as non-liquefiable and seismically stable for the planned construction.